Ewolucja paradygmatu datacentrycznego w aspekcie integracji systemów informatycznych przedsiębiorstw - Niesler, Andrzej (Evolution of the Data-Centric Paradigm in Management Information Systems Integration, 2007)
The data-centric paradigm is one of the most important and commonly used engineering approach. In the age of global networks, distributed processing and rapid information interchange, the data characteristics have altered, and so has altered the data-centric paradigm. The change has crucial impact on the process of management information systems' integration and should be taken into consideration not only by information or integration officers, but also enterprise executives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 149-158